2015
DOI: 10.1186/s12891-015-0768-y
|View full text |Cite
|
Sign up to set email alerts
|

A screening tool for non-specific low back pain with disability in office workers: a 1-year prospective cohort study

Abstract: BackgroundHaving a screening tool with reasonable predictive ability is essential in providing information about an individual’s risk of developing a disease, allowing an examination to be conducted with limited personnel and time, and selecting the relevant individuals for therapeutic research. This study aimed to produce a screening tool to identify office workers at risk of developing non-specific low back pain (LBP) with disability, and to evaluate the tool’s predictive power.MethodsAt baseline, 615 health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…[29,30,35,56,64,65] ROC AUC for the VAS ranges from 0.71 to 0.93. [35,61,[66][67][68] Our results are within these ranges at six-weeks for all but our VAS estimate at one-week, where our estimate approaches the lower border of the range.…”
Section: Comparison With Prior Worksupporting
confidence: 76%
“…[29,30,35,56,64,65] ROC AUC for the VAS ranges from 0.71 to 0.93. [35,61,[66][67][68] Our results are within these ranges at six-weeks for all but our VAS estimate at one-week, where our estimate approaches the lower border of the range.…”
Section: Comparison With Prior Worksupporting
confidence: 76%
“…A study revealed that long-time sedentary work, high workload, and inappropriate sitting arrangements are the contemporary causes of LBP [10]. Many studies conducted with office workers found a relationship between sitting and LBP [6,[11][12][13][14][15]. Another study suggested that the associated factors of LBP for office workers were: long office hours, working in the same posture, and continuing the same job for many years [3].…”
Section: Introductionmentioning
confidence: 99%
“…ROC AUC for the NRS ranges from 0.67 to 0.93 [ 41 , 42 , 47 , 67 , 75 , 76 ]. ROC AUC for the VAS ranges from 0.71 to 0.93 [ 47 , 72 , 77 - 79 ]. Our results are within these ranges at 6 weeks for all instruments and for all but our eVAS instrument at 1 week, where our point estimate approaches the lower border of the range.…”
Section: Discussionmentioning
confidence: 99%